Pendidikan Karakter untuk Membangun Anak Didik yang Memiliki Keseimbangan IQ, EQ dan SQ - Hafni, Nurlaili Dina; Shofwan, Arif Muzayin; Laila, Khamidatul; Arifin, Triananda Zainal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Character education is not only to build students who have pseudo-politeness. However, character education also aims to build students who have a balance of IQ, EQ, and SQ. This qualitative descriptive research with literature study discusses character education which aims to build students to have a balance of IQ, EQ, and SQ. The data analysis technique uses content analysis by sorting out data according to the research objectives. This paper produces several things as follows. First, the purpose of character education, of which is to form a nation that is tough, competitive, has a noble character, moral, tolerant, have a patriotic spirit, develop dynamically, is oriented to science and technology, and is inspired by faith and piety to God based on Pancasila, encourages students to able to independently improve and use knowledge, examine and internalize and personalize character values ​​and noble character so that they are manifested in daily behavior. Second, how to build students who are balanced in terms of IQ, EQ, and SQ, one of which is to apply several benchmarks as follows, including love of God and the universe; responsibility, discipline, and independence; tolerance and love of peace towards others; kind and humble; leadership and justice; self-confidence, creativity, hard work, and never give up; affection, care and cooperation; respect and courtesy; and honesty.